IMPLEMENTATION OF FUZZY CONTROL ALGORITHM FOR PHOTOVOLTAIC ARRAY MAXIMUM POWER POINT TRACKING - Wójtowicz, Stefan; Zawistowski, Maciej (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
Due to the non-linear characteristics of the current I and voltage U, a PV plant should be equipped with a maximum power point tracking algorithm. This allows obtaining the maximum amount of energy in a large range of illumination. Presently there are many algorithms for determining the maximum operating point of the photovoltaic power plant. This paper is aimed to present the determination of the maximum operating point of the photovoltaic power plant using fuzzy control.